Pengaruh Literasi Keuangan dan Sosialisasi Trhadap Minat Berinvestasi Mahasiswa Di Pasar Modal Syariah Melalui Galeri Invesasi Syariah: Studi Pada Mahasiswa MKS UIN Sayyid Ali Rahmatullah Tulungagung - Amanda Laily Yuniawati; Binti Nur Asiyah (CV ODIS, 2022)
This study aims to determine the effect of financial literacy and socialization on student investment interests. The data was collected through a questionnaire from the students of the Faculty of Economics and Business UIN Sayyid Ali Rahmatullah Tulungagung whose criteria had been determined to get representative results. The data analysis method used is multiple linear regression analysis, an analysis of the coefficient of determination. The results of the study show that financial literacy (X1) has no significant effect on students' investment intentions. Meanwhile, socialization (X2) has a significant influence on the investment interest of UIN Sayyid Ali Rahmatullah Tulungagung students. The practical implications are for students of Islamic financial management study programs to improve financial literacy for students to increase investor interest.